Assessment of Health-Related Quality of Life in Adult Spinal Muscular Atrophy Under Nusinersen Treatment—A Pilot Study - Thimm, Andreas; Brakemeier, Svenja; Kizina, Kathrin; Munoz Rosales, Juan; Stolte, Benjamin; Totzeck, Andreas; Deuschl, Cornelius; Kleinschnitz, Christoph; Hagenacker, Tim (Frontiers in Neurology, 2022)
5q-Spinal muscular atrophy (SMA) is a severely disabling inherited neuromuscular disease that progressively reduces the motor abilities of affected individuals. The approval of the antisense oligonucleotide nusinersen, which has been shown to improve motor function in adult SMA patients, changed the treatment landscape. However, little is known about its impact on patients’ quality of life (QoL), and there is still a need for adequate patient-reported outcome measures. In this study, we used the short form of the Neuro-QoL (Quality of Life in Neurological Disorders) for upper/lower extremity function to prospectively assess the health-related QoL of 17 adult SMA patients prior to initiation of nusinersen treatment and 2, 6, 10, and 14 months afterwards. At baseline, Neuro-QoL scores strongly correlated with motor function scores (Hammersmith Functional Motor Scale Expanded, HFMSE; Revised Upper Limb Module, RULM), but QoL did not increase significantly during the 14-month treatment period despite significant motor improvement as measured by HFMSE. Our results underline the need for novel, disease-specific assessments of QoL in SMA.